1990
DOI: 10.1042/bj2720045
|View full text |Cite
|
Sign up to set email alerts
|

Antibody organization on lipid films. Influence of pH and interchain disulphide reduction

Abstract: Two distinct lattice structures are observed for two-dimensional (2-D) antibody organization on phospholipid films. A low-order, small-unit-cell, square lattice is obtained at pH 7 and below for mouse IgE, mouse IgG2a and IgG2b and rabbit IgG. At pH 7.5 and above, the observed lattice structure switches to a large-unit-cell, hexagonal type for rabbit IgG and mouse IgE. Interchain disulphide reduction by exposure to 2 mM-dithiothreitol results in the formation of the compact 2-D lattice for all cases and for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“… 6–8 While the IgM molecules exist in a pentameric form, the IgG molecules exist in a monomeric form, but it was recently shown that the IgG molecules form a hexamer and the IgG hexamer binds to the complement complex by transmission electron microscopy. 9–11 Recently, we also reported the self-assembly of monoclonal IgG antibodies from mouse 12 using high-resolution atomic force microscopy (AFM) 13–20 ( Fig. 1b ).…”
Section: Introductionmentioning
confidence: 96%
“… 6–8 While the IgM molecules exist in a pentameric form, the IgG molecules exist in a monomeric form, but it was recently shown that the IgG molecules form a hexamer and the IgG hexamer binds to the complement complex by transmission electron microscopy. 9–11 Recently, we also reported the self-assembly of monoclonal IgG antibodies from mouse 12 using high-resolution atomic force microscopy (AFM) 13–20 ( Fig. 1b ).…”
Section: Introductionmentioning
confidence: 96%